PERUBAHAN MUTU BUAH PEPAYA (CARICA PAPAYA L) VARIETAS IPB 9 (CALINA) SELAMA PENYIMPANAN PASCA SIMULASI TRANSPORTASI - Ismaya, Pandu Legawa (Department of Food Technology, Universitas Pasundan, Bandung, 2023)
Papaya (Carica Papaya L.) IPB 9 (calina) variety has thick, sweet flesh and high productivity. During the transportation process of papaya fruit, mechanical damage (bruises, abrasions, weight loss) and physiological damage often occur which can cause papaya fruit to experience a decrease in the quality of papaya during storage before consumption. The purpose of this study was to determine changes in the quality of papaya fruit after transportation simulation. The research design used a randomized block design (RAK) with the treatment of the position of the fruit in the packaging which was stored horizontally (KS1) and vertically (KS2) during the transportation simulation process. After transport simulation, the papayas were stored at 18-20oC for 12 days. The quality measurement results for weight loss after 12 days of storage for KS1 reached 7.34% and KS2 reached 7.43%. The results of hardness measurements after 12 days of storage for KS1 were 0.84 kgf and KS2 were 0.76 kgf. The results of measuring the skin color of papaya fruit after 12 days of storage showed a decrease in the freshness of the papaya fruit but it was still suitable for consumption. The measurement results for the total dissolved solids content after 12 days of storage for KS1 reached 11.45% and KS2 reached 11.32%.